An overview of the utilization of TikTok to improve oral English communication competence among EFL undergraduate students - Xiuwen, Zhai; Razali, Abu Bakar (Horizon Research Publishing, 2021)
The field of English language communication competence learning and acquisition has been revolutionized by the increasing development of technology. The application of social media has now been popular inside and outside of the English language classrooms. The development of technology in the past fifty years, the more recent mobile devices and the Web 2.0 technology have provided numerous opportunities for its use in improving English communication competence. TikTok, one of the popular social media platforms among Chinese international undergraduate students, is now playing an interesting role in their English communication competence learning during Covid-19 pandemic because TikTok supplies English videos with popular topics among youngsters. However, very few studies have been conducted on the utilization of TikTok on EFL undergraduate students' English communication competence. Therefore, this paper aims to explore the potential on the utilization of TikTok and how it impacts on English language communication competence acquisition among Chinese international undergraduate students by reviewing previous and recent studies focusing on TikTok as well as other social medias such as Facebook, YouTube, WeChat and so on. It is important to note that even though previous relevant studies have showcased the positive effects of using social media as learning aids in English language communication acquisition, very few literatures having been published focusing on the utilization of TikTok in English language communication acquisition. The expected findings of this paper could reveal the potential of using TikTok for international undergraduate Chinese students out of EFL classroom in improving their English Communication Competence and for increasing their interests of speaking English. The researchers showcase critical views, recommendations, as well as implications for the utilization of TikTok in the field of English language communication competence acquisition among EFL undergraduate students.